Consciousness and the self : new essays - Liu, JeeLoo; Perry, John, 1943- (Cambridge : Cambridge University Press, 2012)
''I never can catch myself at any time without a perception, and never can observe any thing but the perception.' These famous words of David Hume, on his inability to perceive the self, set the stage for JeeLoo Liu and John Perry's collection of essays on self-awareness and self-knowledge. This volume connects recent scientific studies on consciousness with the traditional issues about the self explored by Descartes, Locke and Hume. Experts in the field offer contrasting perspectives on matters such as the relation between consciousness and self-awareness, the notion of personhood and the epistemic access to one's own thoughts, desires or attitudes. The volume will be of interest to philosophers, psychologists, neuroscientists, cognitive scientists and others working on the central topics of consciousness and the self'--
'In our everyday activities, the self is ever-present in the back of our minds. We remember what we did the moment before and we think about what we want to do next; we feel happy and energetic, or bored and tired; we have a sense of our goals when we act; we think about what we would like to eat for dinner and we know what our favorite TV show is. In our interactions with others, we think about how they see us, whether they like us or are impressed by us. We have certain emotions related to this keen awareness of ourselves: we feel embarrassed, remorseful, ashamed, proud or confident, because of things we have done or did not do. We see ourselves as continuous in time: what happened to us in the past affects who we are and what we believe now; we make plans for the future because we believe that the future self will be us and will be affected by our current plan and behavior'--
Machine generated contents note: Introduction: consciousness and the self; 1. Awareness and identification of self David Rosenthal; 2. Self-representationalism and the explanatory gap Uriah Kriegel; 3. Thinking about the self John Perry; 4. Ordinary self-consciousness Lucy O'Brien; 5. Waiting for the self Jesse Prinz; 6. I think I think, therefore I am - I think: skeptical doubts about self-knowledge Fred Dretske; 7. Knowing what I want Alex Byrne; 8. Self-ignorance Eric Schwitzgebel; 9. Personhood and consciousness Sydney Shoemaker; 10. My non-narrative, non-forensic Dasein: the first and second self Owen Flanagan.
Keywords: Self-consciousness (Awareness)